Open J Dent Oral Health 2019
DOI: 10.36811/ojdoh.2019.110002
|View full text |Cite
|
Sign up to set email alerts
|

The Discourse on Measuring Frequency of Tongue Strength

Abstract: Iowa Oral Performance Instrument (IOPI) is an instrument used to measure tongue strength. The standard protocol of operating IOPI is three trials separated by 10-15 seconds of rest. The highest pressure of these three trials is recorded as the tongue strength. The purpose of this study was to investigate the difference of three trials. Forty-one healthy adults were taken as research subjects. Repeated-measurements analysis of covariance (RANCOVAs) was used to analyze the anterior and posterior tongue strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…In this study, there were 11 muscle measuring procedures, each of which was evaluated for three consecutive trials as recommended in the IOPI user manual, and a total 33 trials for muscle strength measurements. Following the completion of measurements, some participants experienced orofacial muscle soreness for 24 h. Similar results were reported in previous studies with tongue strength measurements [21,22]. Repeated trials had no effect on the measurement of labial and lingual strength parameters; this result was in line with the findings reported by Vanderwegen et al [20].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, there were 11 muscle measuring procedures, each of which was evaluated for three consecutive trials as recommended in the IOPI user manual, and a total 33 trials for muscle strength measurements. Following the completion of measurements, some participants experienced orofacial muscle soreness for 24 h. Similar results were reported in previous studies with tongue strength measurements [21,22]. Repeated trials had no effect on the measurement of labial and lingual strength parameters; this result was in line with the findings reported by Vanderwegen et al [20].…”
Section: Discussionsupporting
confidence: 90%
“…Some participants in a previous study reported feeling orofacial muscle soreness immediately after their tongue strength measurement, and it is described in the Iowa Oral Performance Instrument (IOPI) user manual that a participant who is to perform the tongue strength measurement may experience "throat soreness" due to normal muscle fatigue [21,22]. After the establishment of the reference data for tongue strength in healthy Chinese adults, the tongue strength measurement will be applied in a wide range of clinical practice-for example, with frail patients, individuals with physical disability, or older adults.…”
Section: Introductionmentioning
confidence: 99%